DESENTRALISASI FISKAL: KAJIAN PERBANDINGAN KETIDAKSEIMBANGAN FISKAL VERTIKAL DI INDONESIA DAN JEPANG - Gedeona, Hendrikus (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
This comparative study tries to map several aspects concerning finance relation between central and local government in both countries. The main purpose is to compare fiscal implementation through decentralization policy in the two countries, especially the case of vertical fiscal imbalance. The research focuses on vertical imbalance because it is a common problem in various countries around the world. It also occurs in Japan and Indonesia in line with fiscal implementation through decentralization policy. The analysis will be in the inter-related context of decentralization policy and fiscal decentralization.